Gobernar un mundo en guerra: el rol de los cabildos en el primer orden colonial peruano (1529-1548) - Alarcón Olivos, Marcos (2019)
Although the cabildo was a key institution in the conquest of America, the role it played in the various regions of the continent before the establishment of royal power is not known in detail. This article argues that the establishment of cabildos during the conquest of the Inca Empire allowed the creation of a local Hispanic political space, which enabled the establishment of colonial Peru’s first administrative and government structure. By facilitating the early negotiation and distribution of territorial resources, the institution reduced tensions among members of the expedition and thus provided stability to this first order, even in places that resisted direct control by the current governor. The various leaders of conquest sought to dominate this first order via the cabildos, and to maintain it against the onslaught of their rivals and the Crown.